Pengaruh Word of Mouth, Religiusitas, Behavior Control Terhadap Niat Pembelian Obat Halal - Handayani, Rosa; Setyaning, Alldila Nadhira Ayu (Penerbit Goodwood, 2025)
Purpose: This study investigates the influence of word of mouth, religiosity, and behavioral control on purchase intention for halal pharmaceutical products in Indonesia, with attitude serving as a mediating factor. This research is grounded in the context of Islamic marketing and consumer behavior. Methodology/approach: A quantitative survey method was used to collect data from Muslim consumers in Indonesia. Analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. Results/findings: The findings indicate that word-of-mouth, religiosity, and behavioral control have a significant influence on purchase intention. Additionally, attitude plays a mediating role in the relationship between religiosity and purchase intention, as well as between word of mouth and purchase intention. This suggests that stronger religious beliefs and positive word-of-mouth can shape consumer attitudes, which in turn drive the intention to purchase halal pharmaceutical products. Conclusions: This study found that word of mouth, religiosity, and behavioral control significantly influenced consumers’ intention to purchase halal medicines, with attitude playing a key mediating role. Positive recommendations, strong religious values, and a sense of control all contribute to shaping favorable attitudes and increasing the intention to buy halal pharmaceutical products. Limitations: This study is limited by the availability of literature on halal pharmaceutical consumer behavior, leading to comparisons with other halal product industries. Contribution: This study contributes to Islamic marketing and consumer behavior studies by offering empirical insights into Muslim consumers' decision-making processes. This finding provides practical implications for businesses and policymakers to enhance marketing strategies for halal pharmaceuticals.